Antimicrobial Resistance of Listeria monocytogenes Strains Isolated in Food and Food-Processing Environments in Italy - Antonio Rippa; Stefano Bilei; Maria Francesca Peruzy; Maria Grazia Marrocco; Patrizia Leggeri; Teresa Bossù; Nicoletta Murru (MDPI AG, 2024)
Listeria monocytogenes, along with various other pathogenic bacteria, may show resistance against a broad spectrum of antibiotics. Evaluating the extent of resistance in harmful microorganisms like Listeria monocytogenes holds significant importance in crafting novel therapeutic strategies to mitigate or combat the rise of infections stemming from antibiotic-resistant bacteria. The present work aims to investigate the occurrence of antimicrobial resistance among Listeria monocytogenes strains in meat products (n = 173), seafood (n = 54), dairy products (n = 19), sauces (n = 2), confectionary products (n = 1), ready-to-eat rice dishes (n = 1), and food-processing environments (n = 19). A total of 269 Listeria monocytogenes strains belonging to eight different serovars were tested against 10 antimicrobials. In the classes of antibiotics, most of the strains were resistant antibiotics belonging to the family of β-lactams (92.94%). High proportions of L. monocytogenes isolates were resistant to oxacillin (88.48%), followed by fosfomycin (85.87%) and flumenique (78.44%). The lowest level of resistance was observed against gentamycin (1.49%). A total of 235 strains (n = 87.36%) showed a profile of multidrug resistance. In conclusion, a high occurrence of resistant and multidrug-resistant strains of Listeria monocytogenes was observed among the examined serotypes isolated from different food sources. This understanding enables the adoption of suitable measures to avert contamination and the spread of resistant bacteria via food.